Concentration dependent mitostatic effect and inhibition of cell motibility by different tubulin binding drugs-comparative study - Balabiyev, Arnat (Nazarbayev University School of Science and Technology, 2016)
Here, we demonstrate the comparative effects of nocodazole, taxol and vinorelbine on mitotic progression and cell motility using mouse fibroblasts and three cancer cell lines
Keywords: nocodazole; taxol; vinorelbine; mitotic progression; cell motility